MOSCOW KINDOM AND THE EUROPEAN INNOVATION OF THE TIME OF TROUBLES - T. V. Chernikova (Vestnik MGIMO-Universiteta)
The article is devoted to the examination of the issue of Russian borrowing of military and technical as well as cultural experience of the West at the beginning of the Time of Troubles during the reign of Feodor I Ivanovich (1584-1598), Boris Godunov (1598-1605) and Dmitry the Pretender (1605-1606). One of the channels of the Russian contact with the west-European "powder revolution" and culture was foreigners on Moscow service. A lot of them were the military; doctors of the Tsar had a huge power; some merchants (for example, Jerome Horsey) carried out special orders of the Russian government. The article gives the description of western foreigners' position both, at the beginning of the Time of Troubles, when the Moscow government was interested in western innovation, and after 1606, when the situation changed. The author tries to find out in which areas and what kind of foreign experts were used in Russia; what were the reasons for the use of the Western European experts; what were the results of this phenomenon. While analyzing the "Notes" of foreigners, who were on the Russian service at the beginning of the Time of Troubles, the author examines the achievements of the "common revolution" at the beginning of XVII century.